Descriptive study on the origin and evolution of beta- defensins copy number variable gene using multigenerational family pedigrees - Musa, Nurul Azmah (2019)
Beta-defensins (DEFB) consists of DEFB4, DEFB103, DEFB104, DEFB105, DEFB106, DEFB107, DEFB108, DEFB109, DEFB114, DEFB118, DEFB123, DEFB126 and SPAG11 that are clustering on chromosome 8p23.1. DEFB mainly involves as the first line of defence against microorganism, especially in the mucosal and epithelial tissues. DEFB is one of the copy number variable gene (CNVs) and has been in close association with disease susceptibility especially in higher copy number. DEFB commonly varies between two and seven copies per diploid. Hence, it has been reported that an individual with a higher copy number (more than four) is more susceptible towards psoriasis but protective against HIV disease. Moreover, as DEFB is varying in copy number, for an individual with three DEFB diploid copies, the haploid copies contributed from each parent is ambiguous whether in a combination of 0+3 or 1+2. Thus, family pedigree was used in this study to follow the DEFB segregation in haploid copies from parents to children. The family pedigree is a diagram that listing the members and ancestral relationship in a family and commonly used in the study of human hereditary. Furthermore, pedigree does assist in the determination of the best treatment and clinical decision of an individual as a specific genetic makeup can be determined for each individual as consideration for the personalize medicine. Therefore, in this study, DEFB copy number both in diploid and haploid copies were measured and haplotype transmission from parents to children were followed for all families. Hence, eight (8) multigenerational families consist of four (4) Malay and four (4) Chinese families with a total of 51 individuals were selected to achieve the objectives of this study. The diploid copy numbers of DEFB was quantified using two Paralogue Ratio Tests (PRTs). Additionally, three multiallelic markers; two microsatellites, EPEV1 and EPEV3, and one indel (rs5889219) were used to validate the diploid copy number and to follow the segregation of haploid copies. This present study found DEFB copy number varies between three to six per diploid with five copies as the most common. The copy number is not widely varying due to close-related relationship within the family pedigrees. Segregation analysis from multiallelic markers has been successfully inferred the haploid copies by following the segregation of the alleles throughout the generation except for three (3) families and found DEFB varies between one to four copies per haploid with two and three as the most common. Alleles size range from 171 bp to 189 bp and 135 bp to 145 bp have been noted in EPEV1 and EPEV3 respectively. Meanwhile, allele 185 bp for EPEV1 and 143 bp for EPEV3 continuously appeared in each generation. From the alleles collected, haplotype for each individual was successfully determined by following the inheritance pattern from parents to children in five (5) families. The recombinant event was discovered in one of the pedigrees where the children inherited the recombinant haplotype from the father, but it did not change the DEFB copy number of the affected children. In conclusion, the origin of the DEFB was successfully determined by following the haplotype transmission from the parents to the children. Moreover, DEFB copy number was successfully quantified in both diploid and haploid copies.